Low-Density-Lipoprotein Particle Size Predicts a Poor Outcome in Patients with Atherothrombotic Stroke - Song, Tae-Jin (J Clin Neurol, 2015)
BACKGROUND AND PURPOSE: Low-density lipoprotein (LDL) particle size is considered to be one of the more important cardiovascular risk factors, and small LDL particles are known to have atherogenic potential. The aim of this study was to determine whether LDL particle size is associated with stroke severity and functional outcome in patients with atherothrombotic stroke. METHODS: Between January 2009 and May 2011, 248 patients with first-episode cerebral infarction who were admitted to our hospital within 7 days after symptom onset were prospectively enrolled. LDL particle size was measured using the nondenaturing polyacrylamide gradient gel electrophoresis assay. Stroke severity was assessed by applying the National Institutes of Health Stroke Scale (NIHSS) at admission. Functional outcome was investigated at 3 months after the index stroke using the modified Rankin Scale (mRS), and poor functional outcome was defined as an mRS score of ≥3. RESULTS: The LDL particle size in the 248 patients was 25.9±0.9 nm (mean±SD). LDL particle size was inversely correlated with the degree of cerebral artery stenosis (p=0.010). Multinomial multivariate logistic analysis revealed that after adjustment for age, sex, and variables with p<0.1 in univariate analysis, LDL particle size was independently and inversely associated with stroke severity (NIHSS score ≥5; reference, NIHSS score 0-2; odds ratio=0.38, p=0.028) and poor functional outcome (odds ratio=0.44, p=0.038). CONCLUSIONS: The results of this study demonstrate that small LDL particles are independently correlated with stroke outcomes. LDL particle size is thus a potential biomarker for the prognosis of atherothrombotic stroke.